Progress Report (Tufts Archival Research Center, 2007)
Progress report to the Tobacco Institute Board of Directors for June 1958. Discusses progress on securing location and officers for the TI. Highlights the need to make contacts in Washington, DC and to stay out of health research issues. Summarizes conference attendance.